Penumbra : poems - Shewmaker, Michael (Ohio University Press, 2017)
Penumbra-Michael Shewmaker's debut collection-explores the half-shadows of a world torn between faith and doubt.
Keywords: American poetry -- 21st century.; POETRY -- American -- General.; LITERARY CRITICISM -- Poetry.; POETRY -- General.; American poetry; 2000-2099